PEMANFAATAN RUMPUT LAUT SARGASSUM sp. SEBAGAI BIOSORBEN DALAM PENYERAPAN LIMBAH LAUNDRY - Sarmila pratama Ningsih; Resti Wahyuni; Cindy Grasella Sibuea; Fitrah Amelia (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2022)
The high growth rate of the laundry industry in Batam resulted in high laundry waste generated. One way to reduce the level of pollution due to laundry waste is by absorption using biosorbent from Sargassum sp. Sargassum sp. made in powder form and activated with chitosan to maximize the absorption rate. The purpose of this study was to see the ability of sargassum sp., in reducing the content of TDS (Total Dissolved Solid), EC (Electrical Conductivity), TSS (Total Suspended Solid), and Phosphate. The method used in this research is the experimental method. Analysis of the data used is descriptive. The results obtained on measurements of pH, TDS, EC, TSS and phosphate, showed that for each measurement there was a decrease in TDS, EC, and TSS after adding sargassum sp. Both activated and not compared with before adding sargassum sp. except in the measurement of phosphate the opposite occurs. For EC the decrease ranged from 34-59%, in the TDS measurement there was a decrease in the range of 14-46%. For the measurement of TSS and phosphate, the reductions ranged from 7-99% and 4-68%, respectively. Based on LHRI Regulation No. 5 of 2014 concerning wastewater quality standards, the highest phosphate level is 2 mg/L, TSS 60 mg/L and pH ranges from 6-9, it means that phosphate and pH still meet the standard while TSS before the addition of biosorbent exceeds the standard but after being added sargassum sp. activated to meet the standard except for the unactivated.